Studi perbandingan metode oksidasi enzimatis terhadap aktivitas antioksidan ekstrak air teh kratom (Mitragyna speciosa Korth.) - Brigita Ratna Harsanti; Sulvi Purwayantie; Dzul Fadly (AGROINTEK, 2024)
One of the kratom (Mitragyna speciosa Korth.) products in Kapuas Hulu is fermented kratom tea powder, produced by the enzymatic oxidation process, which is very different from the processing of black tea. Until now, there has been no research on the manufacture of fermented kratom tea powder using the black tea enzymatic oxidation method. This study aimed to determine the differences between the enzymatic oxidation method to the antioxidant activity of water extract kratom tea. The technique used in this study was a comparative method to compare the data obtained from water extract kratom tea. The treatments compared were the manufacture of fermented kratom tea powder with the enzymatic oxidation method of the Kapuas Hulu community and the enzymatic oxidation method of black tea. The parameters tested in this study consisted of phenol content, flavonoid content, alkaloid content, and antioxidant activity. The study showed that the phenol and alkaloid contents were higher in product of black tea methods (199.22 mg GAE/g and 44.73%) than Kapuas Hulu traditional methods (50.45 mg GAE/g and 40.68%). Flavonoid content was higher in Kapuas Hulu traditional methods (169.32 mg QE/g) than black tea methods (48.77 mg QE/g). The difference was found in the antioxidant activity of the water extract kratom tea produced by two different enzymatic oxidation methods. The enzymatic oxidation of the black tea method was found to higher antioxidant activity of water extract kratom tea.